Implementasi Kewenangan Kejaksaan Tinggi Sumatera Barat Dalam Penyitaan Aset Pelaku Tindak Pidana Korupsi Pengadaan Lahan Jalan Tol Di Kabupaten Padang Pariaman - Nisa Riska Wahyu; Elwidarifa Marwenny (GLOBAL SCIENTS PUBLISHER, 2025)
Corruption becomes a culture in Indonesia every year, as the Corruption Perception Index in Indonesia increases every year. Corruption is a serious problem that increases every year. Meanwhile, this has been regulated in Law Number. 31 of 1999 in conjunction with Law no. 20 of 2001 which regulates its eradication. One of the efforts to eradicate corruption is by confiscating the assets of the perpetrators. This confiscation was also implemented by the West Sumatra High Prosecutor's Office in confiscating assets in the Toll Road Land Procurement corruption case in Padang Pariaman Regency. This case is a criminal act of corruption in compensation money for toll road procurement in Padang Pariaman Regency. The formulation of the problem in writing includes: 1) How is the implementation of the authority of the West Sumatra High Prosecutor's Office in confiscating assets of perpetrators of criminal acts of corruption in toll road land acquisition cases in Padang Pariaman Regency; 2) What are the obstacles faced by prosecutors in confiscating goods resulting from corruption in the toll road land procurement case in Padang Pariaman Regency. The aim of this research is to analyze the implementation of the authority to confiscate assets by the West Sumatra High Prosecutor's Office and identify the obstacles faced in this process. This research uses empirical juridical methods with a qualitative approach. The research conclusions show that the implementation of the authority to confiscate assets by the West Sumatra High Prosecutor's Office has been carried out in accordance with applicable statutory provisions, but still faces various obstacles in its implementation. These obstacles include the long process of searching for information at the National Land Agency (BPN), Padang Pariaman and efforts to cover up the assets owned by the defendant.